Transcatheter stenting of the systemic‐to‐pulmonary artery shunt: A 7‐year experience from a single tertiary center. Issue 3 (2nd April 2015) - Vaughn, Gabrielle R.; Moore, John W.; Mallula, Kiran K.; Lamberti, John J.; El‐Said, Howaida G.
<x xml:space="preserve">Abstract</x> Background Systemic‐to‐pulmonary artery shunt (SPS) dysfunction can be deleterious in shunt dependent patients and traditionally have undergone surgical revision. Data on transcatheter stenting of SPS is limited. We sought to evaluate feasibility, safety and outcomes of stenting SPS. Methods Retrospective review of all patients who underwent transcatheter SPS stenting from 1/2006 to 12/2013. Results Of 229 surgically implanted SPS, 25 transcatheter stent interventions were performed in 22 patients. The majority had pulmonary atresia (n = 9) or HLHS (n = 10). Their median age was 4 ms (range 10 days to 4 years) and median weight 4.9 kg (range 3–14). Nine had a central and 15 had a BT shunt with a median shunt size of 3.75 mm (range 3–6). The interval from shunt placement to intervention was 1.9 ms (range 4 days–3.8 years). The indication for intervention was increasing cyanosis in10 patients and delaying final repair in 9. Two patients were on ECMO at the time of intervention. The median shunt diameter increased from 2.3 to 4.1 mm and oxygen saturation from 72 to 85% (P < 0.001). No intra‐procedural complications were encountered. One patient died from aspiration (autopsy demonstrated a patent shunt), 13 progressed to repair or next stage, 6 remain palliated with shunts as they are deemed unfit for the next stage and 2 are awaiting surgery. Conclusions Stenting of systemic to pulmonary artery shunt is a safe and effective procedure and avoids surgical re‐intervention. It can be performed both as a rescue procedure in patients with acute shunt occlusion and as an elective procedure to palliate patients not yet suitable for subsequent corrective or staged repair. © 2015 Wiley Periodicals, Inc.